Bank Owned Life Insurance: A Critical Examination of Banking Strategy (International Journal of Banking and Finance, 2012)
This paper is an investigation of a rampant insurance practice in the US banking sector, namely the permitted practice of employer-paid insurance policy. Under this policy, employee’s life policy paid for by the employer, pays large sums as policy benefits to the employer not to the employee’s family. Employers suggest that taking insurance covers the possible monetary loss value of an employee departing the firm, and hence the benefit is quite permissible, kosher. Our findings show its widespread occurrence in beefing up the earnings and even the capital base of the US banks. It calls into question if this practice, though legal, is socially responsible since an employee with such employer-paid policy would be deprived of tax deduction for his own self-paid policy cover, in most instances. Banking sector’s prevalent use of this practice to cover even low-paid workers such as janitors brings into focus the ethics of this practice.